Experimental Study on Moisture Migration in Unsaturated Sand Under Cyclic Diurnal Temperature Variation - Mao, Xuesong; Zhang, Jianxun; Wu, Qian; Liu, Feifei; Li, Xiangyu; Wang, Yueyue (Frontiers in Earth Science, 2022)
The phenomenon of mixed migration of liquid water and water vapor appeared in subgrade covered with the impermeable semi-arid rigid. The soil-water characteristic curves (SWCC) at different temperatures are a key factor for revealing the mechanism of liquid water migration. In particular, the matric suction of unsaturated soil is considerably affected by the change of temperature. And the moisture migration laboratory experiment can visually observe the moisture migration process. Therefore, matric suction tests with different temperatures and moisture migration of the one-dimensional soil column were conducted. Then the non-isothermal soil-water characteristic curves (SWCC) model was extended based on the VG model, and the validity was given. Based on the above results, the mechanism of the mixed migration of liquid water and water vapor in moisture migration of unsaturated soil under the effect of the cyclic diurnal temperature variation was revealed. The research demonstrated that the matric suction for unsaturated sand decreases with the increase of temperature. During the daytime, the temperature was reduced with the increase of soil layer depth. Except for a part of liquid water transformed into water vapor, the liquid water migrated downward under the action of gravity and matric potential. At night, the water vapor accumulated beneath the lid transformed into liquid water under the action of the temperature sharply decreased, which was the main reason for the moisture aggregate beneath the closed layer. Meanwhile, the liquid water and water vapor mutually transformed and dynamically migrated in soil column under the effect of the cyclic diurnal temperature variation. The moisture in the soil column dynamically migrates between daytime and night, which was named as “moisture circulation of covering effect” in this paper. And the “moisture circulation of covering effect” would progressively attain a dynamic equilibrium and dynamic circulatory between the daytime and night with time.